Effect of Noni (Morinda citrifolia) Fruit Flour on Antioxidant Status and Hematological Indices of Laying Japanese Quail - Adriani , Lovita; Indrayati, Nenden; Rusmana, Deni; Hernawan, Elvia; Rochana, Ana (International Journal of Poultry Science, 2017)
Background and Objective: Nutrition has been reported to have a huge role in maintaining the pro-oxidant-antioxidant balance. Therefore, a study was conducted to evaluate the effect of Noni Fruit Flour (NFF) on antioxidant status and hematological indices of layer quail birds. Materials and Methods: A total of 400, 4 weeks old quail birds were used in this study in a Complete Randomized Design (CRD). The birds were randomly assigned into four treatment groups of P0, P1, P2 and P3 with 25 birds treatment–1 replicated 5 times of 5 birds each. The birds in first group (P0) were given basal feed without noni, while as other groups were supplemented with 0.25% (P1), 0.50% (P2) and 0.75% (P3) NFF. Results: There was a non-significant (p>0.05) reduction in malondialdehyde (MDA) level of quails due to NFF supplementation. A linear reduction in blood MDA levels was observed with increase in level of NFF, with highest reduction (0.340±0.04 nmol mL–1) in group fed 0.75% NFF compared to control (0.390±0.041 nmol mL–1). A statistically non-significant increase in total number of erythrocytes and hemoglobin was found with increase in NFF level. Highest erythrocyte number (3.54±0.395×106 mm–3) and hemoglobin (11.81±4.03 g dL–1) were found in group fed 0.75% NFF. Conclusion: Addition of NFF in diet of quail birds had beneficial effect in reducing the oxidative stress and oxidative damage as reflected by reduced MDA levels and increased erythrocyte number and hemoglobin concentration.